Logistic Regression Analysis of Factors Influencing Mobile Application Adoption in Smallholder Livestock Farming: A Case Study from Northern Thailand - Saengwong, S.; Kongmuang, N.; Intawicha, P.; Sakphoowadon, S. (Tropical Animal Science Journal, 2025)
This study examines the factors affecting the adoption of mobile farming management applications by smallholder livestock farmers in Northern Thailand. Data from 300 farmers were analyzed using binary logistic regression to evaluate 14 independent variables and their influence on application use. Four significant factors were identified: education level, participation in training programs, extension support, and membership in farmer associations. Education and participation in training programs were highly significant (p